2004
DOI: 10.1111/j.1365-2842.2004.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation of marginal accuracy of implant‐supported screw‐retained partial dentures

Abstract: Mismatch occurring during the fabrication of implant-supported dentures may induce stress to the peri-implant bone. The purpose of this study was to investigate the influence of two different alloys and the fabrication method on the marginal accuracy of cast partial dentures. Two laboratory implants were bonded into an aluminium block so that the distance between their longitudinal axes was 21 mm. Frameworks designed for screw-retained partial dentures were cast either with pure titanium (rematitan) or with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
17

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 21 publications
(21 reference statements)
2
29
0
17
Order By: Relevance
“…31,65,67 Strain gauges have been used extensively on bone in vivo or ex vivo and even in coagulum around immediate implants, but the measurements are limited to the area where the gauge is bonded or embedded. 70,72 The use of strain gauge to evaluate stresses induced on the implants is reliable, as observed in the literature (Table 3).…”
Section: Strain Gaugesmentioning
confidence: 86%
See 1 more Smart Citation
“…31,65,67 Strain gauges have been used extensively on bone in vivo or ex vivo and even in coagulum around immediate implants, but the measurements are limited to the area where the gauge is bonded or embedded. 70,72 The use of strain gauge to evaluate stresses induced on the implants is reliable, as observed in the literature (Table 3).…”
Section: Strain Gaugesmentioning
confidence: 86%
“…15,17,67,68 Strain gauges can be used to assess stress in prostheses, implants, and teeth both in vivo and in vitro. [68][69][70][71] Methods based on strain gauges have been used to calculate rather than measure tissue stress and strain. 1 The use of a strain gauge to evaluate the stresses induced in the implants presents clinical reliability.…”
Section: Strain Gaugesmentioning
confidence: 99%
“…The passive fit between prosthesis and implant is an important factor for treatment success to minimize the biological and mechanical failures as retention screw loosening (Ref [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Laser welding has been used to correct ill-fitting implant-supported frameworks4 and may decrease the strains transferred to the implant-bone interface 5. Previous studies found that laser welding of implant-supported frameworks is capable of reducing the prosthetic misfit 4,6-8. The diagonal section of one-piece castings for laser welding reduces the misfit levels of implant-supported frameworks 9,10.…”
Section: Introductionmentioning
confidence: 99%